2015
DOI: 10.1002/dc.23326
|View full text |Cite
|
Sign up to set email alerts
|

Malignancy risk for the categories: Non‐diagnostic, benign, atypical, suspicious, and malignant used in the categorization of endobronchial ultrasound guided‐fine needle aspirates of pulmonary nodules

Abstract: The diagnostic categories are associated with increasing risk of malignancy running from non-diagnostic to malignant. The non-diagnostic category has a significant risk of malignancy. While the risk of malignancy for a benign diagnosis is substantial (24%), it is significantly less than that associated with an atypical or suspicious diagnosis. A suspicious diagnosis carries a risk for malignancy essentially the same as a malignant diagnosis. The categories atypical and suspicious appear to have substantially d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…Nevertheless, until now there was no widely accepted categorization system for respiratory cytology, providing rational patient management in this setting. Therefore, the PSC has proposed new guidelines comprising a standardized classification of respiratory lesions with an associated risk of malignancy . In the current study, 1290 respiratory cytology cases were retrospectively reclassified in accordance with the new PSC guidelines and we analyzed the associated risks of malignancy for each category.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, until now there was no widely accepted categorization system for respiratory cytology, providing rational patient management in this setting. Therefore, the PSC has proposed new guidelines comprising a standardized classification of respiratory lesions with an associated risk of malignancy . In the current study, 1290 respiratory cytology cases were retrospectively reclassified in accordance with the new PSC guidelines and we analyzed the associated risks of malignancy for each category.…”
Section: Discussionmentioning
confidence: 99%
“…The use of multiple modalities of obtaining the diagnostic material had an effect in the assessment of ROM in the different diagnostic categories. On the contrary of previous studies that were mostly designed based on just one technique, EBUS‐FNA, our study evaluated different cytological specimens. Regarding the effect of the different sampling techniques on the results, in Table , the ROM was also analyzed for each category.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Head and neck surgeons sometimes feel uncomfortable about the indeterminate diagnosis, and even doubt the value of FNA in accurately distinguishing benign and malignant salivary gland tumors . It has to be mentioned in this context that FNA diagnoses of other organ systems, including thyroid, pancreas, and lung, all include indeterminate categories . Clinical decisions after cytological indeterminate diagnoses in these organ systems are well established and well accepted by physicians of multiple disciplines.…”
Section: Introductionmentioning
confidence: 99%
“…It also has been demonstrated that rapid on‐site evaluation and molecular testing of cytologic specimens, such as endobronchial ultrasound‐guided fine‐needle aspiration specimens, are essential for clinical decision making in patients with lung cancer …”
Section: Pathology Research In the Era Of Big Datamentioning
confidence: 99%